2006
DOI: 10.1002/hep.21145
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of endoscopic treatment of acute gastric variceal hemorrhage: N-Butyl-2-Cyanoacrylate injection versus band ligation

Abstract: Progression of gastric variceal hemorrhage (GVH) is poorer than esophageal variceal bleeding. However, data on its optimal treatment are limited. We designed a prospective study to compare the efficacy of endoscopic band ligation (GVL) and endoscopic N-butyl-2-cyanoacrylate injection (GVO). Liver patients with cirrhosis with or without concomitant hepatocellular carcinoma (HCC) and patients presenting with acute GVH were randomized into two treatment groups. Forty-eight patients received GVL, and another 49 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
250
4
14

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(275 citation statements)
references
References 40 publications
7
250
4
14
Order By: Relevance
“…21 The preferred first line treatment for acute gastric variceal bleeding is endoscopic obliteration with NBC. 20,22 Endoscopic injection of tissue glue for gastric variceal bleeding was first reported in 1986 by Soehendra et al 12 Since then, this method has been adopted widely and proved to be effective in the hemostasis of gastric variceal bleeding. [23][24][25][26][27][28]30 NBC, a liquid monomer, undergoes rapid exothermic polymerization on contact with living tissues, and this property of the compound has been used to eradicate and treat GV.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21 The preferred first line treatment for acute gastric variceal bleeding is endoscopic obliteration with NBC. 20,22 Endoscopic injection of tissue glue for gastric variceal bleeding was first reported in 1986 by Soehendra et al 12 Since then, this method has been adopted widely and proved to be effective in the hemostasis of gastric variceal bleeding. [23][24][25][26][27][28]30 NBC, a liquid monomer, undergoes rapid exothermic polymerization on contact with living tissues, and this property of the compound has been used to eradicate and treat GV.…”
Section: Discussionmentioning
confidence: 99%
“…The relative efficacy of glue injection in the control of active gastric variceal bleed has been addressed in three randomized trials; it has been compared to sclerotherapy in one trial and variceal ligation in two. 22,24 Two trials demonstrated better control of bleed with the use of glue injection as compared to sclerotherapy or variceal ligation (89% vs. 62% and 87% vs. 45%) 27 ; the third showed equivalent results as variceal ligation. 22 Rebleed was significantly lower with glue injection when compared to variceal ligation (31% vs. 54%) 22,28 and similar to sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations